Development of an RT-RPA assay for La Crosse virus detection provides insights into age-dependent neuroinvasion in mice - Lumkong, Lily; Alatrash, Reem; Sridhar, Sainetra; Tonto, Prince Baffour; Herrera, Bobby Brooke (Virology journal, 2025)
Background La Crosse virus (LACV) is a mosquito-borne arbovirus responsible for pediatric encephalitis in North America, predominantly affecting children under 16 years. Early and accurate diagnosis is critical to reducing morbidity in this vulnerable population. However, existing molecular and serological methods are limited in sensitivity, specificity, and accessibility. Methods To address these limitations, we developed a reverse transcription recombinase polymerase amplification (RT-RPA) assay for LACV detection. Primers targeting the divergent M segment of the LACV genome were designed and screened for optimal performance. The assay’s analytical sensitivity was evaluated through serial dilutions of LACV RNA prior to reverse transcription, while specificity was assessed using reverse transcribed RNA from related or geographically relevant arboviruses. We further adapted the RT-RPA test into a lateral flow assay (LFA) format for potential point-of-care use. Additionally, we employed a murine model to explore the age-dependent dynamics of LACV neuroinvasion and clearance, with the virus detected using RT-RPA and reverse transcription quantitative polymerase change reaction (RT-qPCR). Results Primer screening identified an optimal primer pair that amplified LACV cDNA within 20 min at 39 °C, with a limit of detection (LOD) of 100 copies. The assay demonstrated high specificity, with no amplification of related or other geographically relevant arboviruses. Integration of the RT-RPA test into an LFA format preserved the LOD and specificity, enabling visual detection via test strips. In the murine model, weanling mice exhibited LACV neuroinvasion as early as 4 days post-infection (dpi), with sustained detection between 5 and 7 dpi. In adult mice, neuroinvasion was first detected at 5 dpi, plateauing between 6 and 10 dpi, and cleared entirely by 20 dpi in surviving animals. Conclusions This study establishes the RT-RPA assay as an efficient, specific, and sensitive diagnostic platform for LACV, with potential for adaptation into field-deployable LFA tests. Moreover, our findings provide valuable insights into the age-dependent dynamics of LACV neuroinvasion and clearance, informing future diagnostic and therapeutic strategies.